The dual carbon emission effects of digital economy: Evidence from China - Yanze Wang; Zhi Su; Xuanye Cai; Jian Yu (Heliyon)
Nowadays, the digital economy has become a new engine of economic growth around the world. How to utilize the digital economy to achieve a balance between economic development and carbon emissions reduction is an imperative yet challenging endeavor for developing countries. In this paper, based on two perspectives of digital economy, the digital industrialization and industrial digitization, we use the industrial and city-level data of China from 2002 to 2017 to analyze the dual effects of digital economy on carbon emission, carbon intensity and carbon inequality. The results show that the two branches of the digital economy have different impacts on carbon emissions with varying influence mechanisms. The industrial digitization increases the carbon emissions of traditional industries but reduces their carbon intensity and carbon inequality by influencing energy intensity and net profit. While the digital industrialization increases urban carbon emissions and reduces urban carbon inequality through increasing energy intensity and optimizing industrial structure. Following the evidence from China, developing countries can allocate resources for digital industrialization or industrial digitization according to their own resource endowment and industrial status, thereby realizing the co-development of the economy and climate governance under limited resources.